Population Variation and Distribution of Chukar Partridge Alectoris chukar (Gray) in Pauri Garhwal, Western Himalaya - Bisht, M. S.; Kukreti, M.; Dobriyal, A. K. (Indian Forester, 2010)
Distribution, ecology, population and habitat use of Chukar partridge, Alectoris chukar was studied in district Pauri Garhwal, Uttarakhand during 2008 and 2009. A total 1932 individuals in 498 groups were recorded in 16 sites with an over all mean of 7.78±2.07 individuals per sighting and density of 5.31±0.86 birds/km2. The group size estimated was 5.77±0.89 between 720 and 2000m altitudes. Maximum sightings of the birds were recorded on the south-east facing slopes covered with chir pine, mixed pine forests, scrub near the crop fields. Intensive study showed distinct seasonal variation in population, group size and habitat use across the seasons. Large group sizes were observed during the monsoon and post monsoon season. Chukar found to use all types of habitats but the scrub and crop fields are most preferred in Pauri Garhwal.